Impact of Acute Kidney Injury in Patients with Acute Decompensated Heart Failure: Cardiorenal Syndrome - Tandel, Sagar; Mishra, Ashish; Jain, Sharad; Sharma, Vishal; Kanabar, Kewal; Vyas, Pooja; Patel, Krutika; Desai, Nisarg; Kedia, Aman (Jurnal Kardiologi Indonesia, 2025)
In “Impact of Acute Kidney Injury in Patients with Acute Decompensated Heart Failure: Cardiorenal Syndrome” (Indonesian Journal of Cardiology, 44(2), 75-86. https://doi.org/10.30701/ijc.1561), there are an errors noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1561. The error occurs only in the PDF; the DOI listed in the article metadata is already correct. An error was also found in the author's name, Sagar Tandel. We have corrected the author name from “Sager Tandel” to “Sagar Tandel”.The publisher apologizes for any inconvenience caused by this error.DOI of original article: https://doi.org/10.30701/ijc.1561